2018
DOI: 10.3390/w11010013
|View full text |Cite
|
Sign up to set email alerts
|

Drought Characteristics and Its Response to the Global Climate Variability in the Yangtze River Basin, China

Abstract: The frequent occurrence of drought events in humid and semi-humid regions is closely related to the global climate variability (GCV). In this study, the Standard Precipitation Evapotranspiration Index (SPEI) was taken as an index to investigate the drought in the Yangtze River Basin (YRB), a typical humid and semi-humid region in China. Furthermore, nine GCV indices, such as North Atlantic Oscillation (NAO) were taken to characterize the GCV. Correlation analysis and a joint probability distribution model were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…Precipitation plays a significant role in water level fluctuation. A previous study indicated that the summer monsoon strongly influences the middle and lower reaches of the Yangtze River, thus leading to abundant precipitation and making the area humid [12]. A contour image of monthly precipitation during 1967-2018 shows heavy precipitation was concentrated between April and September with June as the peak value ( Figure 5), which is similar with the phenomenon in the Yellow River [13] and Dongting Lake located at the middle of the Yangtze River [4].…”
Section: Relationship Between Precipitation and Water Levelsupporting
confidence: 66%
“…Precipitation plays a significant role in water level fluctuation. A previous study indicated that the summer monsoon strongly influences the middle and lower reaches of the Yangtze River, thus leading to abundant precipitation and making the area humid [12]. A contour image of monthly precipitation during 1967-2018 shows heavy precipitation was concentrated between April and September with June as the peak value ( Figure 5), which is similar with the phenomenon in the Yellow River [13] and Dongting Lake located at the middle of the Yangtze River [4].…”
Section: Relationship Between Precipitation and Water Levelsupporting
confidence: 66%
“…In the scope of continuation of research on the effect of different teleconnection patterns, it seems necessary to introduce more advanced statistical analyses. An attempt of such research was conducted by among others [90]-the authors analyzed the effect of variability of climate features (expressed in among others NAO and ENSO indices) on values of the SPEI index (Standard Precipitation Evapotranspiration Index) in the Yangtze River Basin, with the application of combined distribution calculated on the basis of Copula functions. Even more advanced computational methods (like machine learning and artificial neural networks) can be used to predict future values of given hydro-and meteorological variables.…”
Section: Discussionmentioning
confidence: 99%
“…Key teleconnection factors linked to the rainfall over Africa are North Atlantic Oscillation (NAO), El Niño Southern Oscillation (ENSO), Atlantic Meridional Mode (AMM), and Atlantic Multidecadal Oscillation (AMO), among others. On drought, ENSO is known to have played a significant role in contributing to drought occurrence at different timescales in the US and Columbia [13][14][15]. In West Africa, the prolonged drought situation in the Sahel was connected to the influence of large ocean-atmosphere climate indices like ENSO, AMO, and Tropical Atlantic Oceanic indices [16].…”
Section: Introductionmentioning
confidence: 99%